Pediatric eosinophilic granulomatosis with polyangiitis and intracardiac thrombus: A case report - Katharine V. Jensen; Nicholas Brochez; Christopher Spence; Joel Livingston; Michael Khoury; Jeanine McColl (SAGE Open Medical Case Reports)
Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare systemic necrotizing vasculitis marked by eosinophilia and extravascular granulomas, predominantly affecting the respiratory tract. This report details a unique EGPA case in a 6-year-old girl with extensive cardiac involvement, featuring an atypical intracardiac mass suggestive of endomyocardial fibrosis and a concomitant thrombus. The clinical course unfolded in three phases: an initial prodrome with asthma; subsequent peripheral hypereosinophilia; and ultimately systemic vasculitis. Cardiac involvement, notably an intracardiac mass in the right ventricular apex extending into the interventricular septum, underscored the diverse nature of EGPA. The patient fulfilled sufficient criteria outlined by the American College of Rheumatology and the European Alliance of Associations for Rheumatology for an EGPA diagnosis, displaying hypereosinophilia, obstructive airway disease, and biopsy-confirmed inflammation predominantly characterized by extravascular eosinophils. Treatment included high-dose methylprednisolone and cyclophosphamide, which resulted in clinical improvement and inflammatory marker normalization. To halt right ventricular thrombus progression, therapeutic unfractionated heparin was initiated, and she was transitioned to warfarin, which resulted in complete resolution of the cardiac mass. This case highlights the necessity of a multidisciplinary approach for managing complex EGPA manifestations, particularly in pediatrics, and emphasizes the importance of timely intervention in mitigating the impact of cardiac complications associated with EGPA.